2013
DOI: 10.1159/000355162
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Chemoradiotherapy and Antiretroviral Therapy for HIV-Infected Patients with Locoregionally Advanced Non-Small Cell Lung Cancer: Benefit and Tolerability of Treatment in 2 Cases

Abstract: Background: Human immunodeficiency virus (HIV)-infected patients are surviving longer since the advent of antiretroviral therapy. Therefore, more patients are developing non-AIDS-defining cancers which increasingly determine mortality. Case Reports: Here we present 2 cases of locally advanced non-small cell lung cancer treated initially with concomitant chemoradiotherapy and antiretroviral therapy. Both patients were male, ages 69 and 66, with known HIV infection and immunologically stable on antiretroviral th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, appropriate clinical practice, including optimal dosages, remains uncertain for cancer patients with HIV and fragile bone marrow function [7]. Conversely, it has also been reported that standard therapy for HIV-positive lung cancer patients undergoing ART achieve good outcomes, which are similar to those seen in HIV-negative patients with advanced NSCLC [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…However, appropriate clinical practice, including optimal dosages, remains uncertain for cancer patients with HIV and fragile bone marrow function [7]. Conversely, it has also been reported that standard therapy for HIV-positive lung cancer patients undergoing ART achieve good outcomes, which are similar to those seen in HIV-negative patients with advanced NSCLC [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…An additional study was retrieved after cross-referencing. Among them, 21 studies, published between 1998 and 2021 were included: 12 assessed the efficacy and/or toxicity of chemotherapy [12][13][14][15][16][17][18][19][20][21][22][23], six described immunotherapy [24][25][26][27][28][29], three reported on tyrosine kinase inhibitors (TKIs) [20,30,31], and eight assessed radiotherapy [13][14][15][16][17]20,22,32]. They included a total of 543 patients with lung tumors, of which 513 with NSCLC.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Four of the studies were from North America (all from the USA) [14,24,26,28], 11 from Europe [12,17,18,25,31,29], one from Europe and the USA [13], and 5 from Asia (all from Japan) [16,20,21,30,32] -Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent chemoradiotherapy was the most common reason among patients deemed unfit for standard care. However, 3 patients recently received chemoradiotherapy concurrent with platinum-doublet chemotherapy (18), without reported severe toxicity or treatment-related deaths.…”
Section: Characteristics Of Hiv-infected Patientsmentioning
confidence: 99%